Biophilic design in improving the psychological performance of University students: A Systematic Literature Review (SLR) / Puteri Sidrotul Nabihah Saarani ... [et al.] - Saarani, Puteri Sidrotul Nabihah; Mohamed Yusof, Nur Fatiha; Ku Azir, Ku Mohammad Asyraf (2022)
As a result of the COVID-19 pandemic that occurred since March 2020, many organisations throughout the world have been obliged to completely adopt a range of emerging online communication platform technologies. University is one of these organisations that has required students and lecturers to use a variety of online communication channels to maintain a continuous educational process. However, the COVID-19 pandemic has resulted in several significant negative psychological effects, including tension, anxiety, and panic attack that happen to students during online learning. It happens to university students due to many internal and external factors like the financial problem, inconducive study area, isolated online learning, and the increasing COVID-19 case. Hence, the purpose of this paper is to review the psychological performance of University students towards the biophilic design study area. The Systematic Literature Review (SLR) method using 11 article papers was applied to achieve the aim and objectives of the research. Findings from SLR was analysed based on content analysis produced from the paper review and discovered that biophilic design can reduce stress, provide happiness and improve concentration and productivity. This paper provides the basis of reference for the student on how biophilic may help them to improve their psychological performance such as emotion, wellness, and productivity during online learning.